1α, 25(OH)2D3(VD3) promotes Raddeanin A-induced anti-proliferative effects on HeLa cell apoptosis and autophagy through negative regulation of HPV18E6-E7/PD-L1/VDR axis. Issue 1 (1st January 2022) - Li, Zhiyu; Xu, Biyun; Sun, Yuexin; Zhou, Lanbo; Tao, Yue; Hou, Wenjun; Bao, Jun; Liu, Jun; Fan, Weixin
ABSTRACT: Raddeanin A (RA) has indicated suppressive effects on various human tumor cells, and insufficient vitamin D was associated with human papillomavirus (HPV) persistence and gynecological tumors. However, combined effects of RA and vitamin D on HPV-positive cells remain elusive. Herein, we aimed to investigate the combined effects of RA and 1ɑ, 25(OH)2 D3 (VD3) on cellular viability and modulation of HPV18E6/E7, programmed cell death 1 ligand (PD-L1) and vitamin D receptor (VDR) expression in HeLa cells in vitro . HeLa cells were treated with RA alone or VD3 combined with RA. Cell viability was measured using 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2-H-tetrazolium bromide (MTT), and apoptosis was detected by flow cytometry. Real-time PCR (qRT-PCR) and Western blot were used to determine the gene/protein expression levels. The autophagosomes were observed by Transmission electron microscopy (TEM). The result showed that cell viability was inhibited by RA, and apoptosis in HeLa cells treated with RA was elevated accordingly. The expression of Bax, Cleaved-caspase-3, Cleaved-caspase-9 and Cleaved-PARP increased, and Bcl-2 decreased. The autophagy was induced by RA, as evidenced by elevated autophagosomes and the increased LC3-II/I ratio and Beclin-1. The expression of HPV18E6/E7, PD-L1 and VDR was reduced by RA. Moreover, RA combined with VD3 had a stronger effect on HeLa cells than RA alone. In conclusion, RA inhibits HeLa proliferation and induces apoptosis and autophagy via suppressing HPV18E6/E7, PD-L1 and VDR, and VD3 showed reinforced effects of RA on HeLa cells. Therefore, combined usage of VD3 with RA might be a potential novel immunotherapy strategy for HPV-related diseases. Graphical abstract: RA and VD3 promotes HeLa cell apoptosis and autophagy by modulating HPV18E6-E7/PD-L1/VDR expression: uf0001